Rancang Bangun E-Commerce Berbasis Website (Study Kasus TB. Pilar Mas Kec. Wongsorejo): Rancang Bangun E-Commerce Berbasis Website (Study Kasus TB. Pilar Mas Kec. Wongsorejo) - Kholiq, Nur; Baijuri, Achmad; Santoso, Firman (Universitas Muhammadiyah Riau, 2024)
A building shop is a business that provides various kinds of materials, equipment and supplies used in construction, renovation, repair and maintenance of buildings. Pilar Mas building shop is a building shop that sells various material products. The transaction system carried out by the Pilar Mas building shop is still traditional. With this method, the transaction process takes quite a lot of time and energy. By building this e_commerce system, it aims to save time and make it easier for workers to carry out transactions. The methodology used in building this e_commerce system is SDLC with a waterfall model because it has structured and systematic stages starting from analysis, design, code creation, testing and maintenance. The result of building this e_commerce system is that it is a medium that makes things easier for sellers and buyers